KEBIJAKAN PENGEMBANGAN USAHA PERIKANAN TANGKAP KOTA DUMAI PROVINSI RIAU - Hazmi Arief; Novia Dewi; Jumatri Yusri (Berkala Perikanan Terubuk, 2014)
This research aimed to determine contribution and base level fisheriessector, sustainability potention and forms of fishing effort management in Dumaiaccording biological and economic aspects and form of capture fisheriesinstitutional development in Dumai. This research used survey method bypurposive sampling. The analysis method was conducted by Shift Share, LocationQuotient, Bioeceonomic Model, Stakeholder Analysis, Policy Analysis (PRA),Descriptive Analysis of policy formulation for sustainable fishery resourcesdevelopment. Macroeconomic analysis indicated that fisheries sector was thedevelopment bases which provide significant contribution to economic growth ofDumai that was strongly influenced by activity of capture fisheries production sothat can served as a regional economic development policy priorities. Accordingto bioeconomy analysis of three products fisheries resources ( shrimp, fish source,lomek ), the utilization of fishery resources in Dumai. The result of this researchalso obtained optimal management regime by used MEY management or SoleOwner. Stakeholder involved in this policy were KKP, DPKP and localgoverment. Policy analysis (PRA) based on Matrix Ranking concluded thatcarrying out the policy directives of quality development and human resourcesquality assosiated with development of training and educational programs forlocal fishermen in improvement of quality and value added of fishery product.This research concluded that the proper policy to be implemented in Dumai wasoptimal improvement / optimization the production of sustainable fisheryresources through provision the conducive fishery facilities in order to increaseparticipation and stakeholders synergy to prosperity. Optimization of fisheryresources productivity need support of all stakeholders to achieve co-managementin order to achieve public prosperity.Keywords : Shrimp, Fish Source, Lomek, Policy Analysis, Fishery Resources,Bioeconomic, Sustainability, Dumai, Riau